An evangelical voice in Africa: the worldview background of the theology of Tokunboh Adeyemo (1 October 1944-17 March 2010) - Van der Walt, B. J. (In die Skriflig, 2011)
Africa was blessed with a son of the calibre of Dr Tokunboh Adeyemo. Since he only recently passed away, we do not yet have (as far as the author is aware) an assessment of the legacy of this eminent Christian leader. This article is the first preliminary evaluation written from a reformational worldview perspective. The set-up of the investigation is as follows: Firstly, a brief outline is given of his life history, especially his training in the Evangelical tradition. Then, the décor (the overall situation of African Christianity) that was the background against which he lived and worked is painted. Thirdly, it is followed by the strengths and weaknesses of Evangelical Christianity of which Adeyemo was a representative. Fourthly, it is indicated how Adeyemo thought in line with post-Lausanne Evangelicalism. In the fifth place a preliminary worldview evaluation of his legacy is given. To assist possible future research a bibliography of his most important publications concludes the investigation.
free
Keywords: Adeyemo; Tokunboh; 1944-2010; Africa – Church history; Theologians; African; Theology; Ecumenical; Theology; Evangelical